Identifying the Utilization of ICT-Based Interactive Media in School during Pandemic Covid-19 - Pratama, Krisna Raditya; Yamtinah, Sri; Roemintoyo, Roemintoyo (Journal of Education Reseach and Evaluation, 2023)
The Covid-19 pandemic has had a very significant impact on paradigm shifts and learning activities. Currently, ICT has a great opportunity to be utilized and contribute optimally to facilitate students during learning activities during the Covid-19 pandemic. The main purpose of this research is to analyze specifically the teacher's views regarding the implementation and use of ICT-based learning media that takes place during learning from home during the covid-19 pandemic. This research design includes qualitative research. The subjects in this study were subject teachers in high schools. Data collection techniques used questionnaires, observations and interviews, with the instruments being questionnaire items, observation sheets and interview guidelines. Data from the questionnaire were analyzed by triangulation, through data reduction, data presentation, and drawing conclusions. The results showed that so far teachers use media as learning aids in the form of printed modules, and assignment sheets, besides the lecture method and presentation media also dominate in the continuity of learning activities, teachers still persist not to use ICT in the learning process, especially to support the independent learning process during the covid-19 pandemic. Innovation through the integration of ICT in the learning process is an important thing for teachers have to do, especially now that students are carrying out learning from home, so that students will remain enthusiastic and motivated to carry out a series of independent learning activities.